Management of lung cancer in older people - Audisio, Riccardo A. (Imprint: Springer, 2013)
The risk of cancer increases with age and the number of older adults seeking treatment is rising dramatically in line with the aging population. The care of older patients differs from that of younger adults because of variation in the biology of the tumor, age-related variation in host physiology, co-morbidity burden and psychosocial issues, which might impact the efficacy and side effects of cancer therapy.   Management of Lung Cancer in Older People focuses on treatment strategies of lung cancers and provides guidance on the issues specific to older patients, spanning background and epidemiology, special considerations in the care of older people, therapeutics, and psychosocial considerations. This book offers a thorough review of current approaches to treating older lung cancer patients, detailing the special issues and considerations involved. The discipline-spanning coverage outlines best practice and proposes topics for future research.   The fourth volume in the Management of Cancer in Older People series, this book will be of interest to all surgical oncologists, medical and radiation oncologists, gerontologists, pulmonologists and other members of the multidisciplinary team involved in the care of elderly lung cancer patients.